Fluctuations in coral health of four common inshore reef corals in response to seasonal and anthropogenic changes in water quality - Browne, Nicola; Tay, J.; Low, J.; Larson, O.; Todd, P. (Elsevier, 2015)
Environmental drivers of coral condition (maximum quantum yield, symbiont density, chlorophyll a content and coral skeletal growth rates) were assessed in the equatorial inshore coastal waters of Singapore, where the amplitude of seasonal variation is low, but anthropogenic influence is relatively high. Water quality variables (sediments, nutrients, trace metals, temperature, light) explained between 52 and 83% of the variation in coral condition, with sediments and light availability as key drivers of foliose corals (Merulina ampliata, Pachyseris speciosa), and temperature exerting a greater influence on a branching coral (Pocillopora damicornis). Seasonal reductions in water quality led to high chlorophyll a concentrations and maximum quantum yields in corals, but low growth rates. These marginal coral communities are potentially vulnerable to climate change, hence, we propose water quality thresholds for coral growth with the aim of mitigating both local and global environmental impacts.